The effectiveness of red ginger extract to decreasemenstrual pain level in adolescent at Al Husna 2 Islamic Boarding School Kediri year 2016 - Rochmanita Sandya Afindaningrum; Rahma Kusuma dewi (International Journal of Health Science and Technology, 2019)
Dismenorea is menstrual problems that is oftenexperienced adolescent and is caused by the occurence of uterine contractions due to increased prostaglandin. The content of gingerol in ginger red can overcome dysmenorrhoea by blocking prostaglandin. The purpose of this study was to know the effect of red ginger drink to the decline in the level of menstrual pain (in adolescent at Boarding school Al Husna 2 Kediri. Pre-experimental research design used by the approach of one group pretest posttest design. The population of this study was all students who experience dismenorea. Sample of adolescents who experience dismenoreawere 17 people with accidental sampling. The average pain score before treatment was 2.53, after treatment average pain score was 1, 59 based on the description, it shows that there was a decrease in pain scores of 0.94 or 37.1%. Normality test is known that the distribution of data in pain scores before being treated distribution is not normal with a p-value of 0.05 while after treated with distribution data is not normal P 0.05, making the results statistically using the Wilcoxon test showed the value of P = 0.000 (p α = 0,05). There is an influence of red ginger drink to the decline in the level of menstrual pain (dysmenorrhoea) in adolescent at Boarding school Al Husna 2 Kediri. Respondents are advised to drink red ginger when dysmenorrhoea.